Metformin Use beyond Diabetes: Reducing Cardiovascular Events in the Healthy Elderly - Xu, Daniel; Affandi, Jacquita; Yap, Timothy; Reid, Christopher (Pacini Editore s.r.l., 2020)
As the global ageing population rises, there is increasing interest and demand for research evaluating anti-ageing strategies. One such strategy involves investigating a drug that may have additional mechanisms and pathways of action to combat ageing - metformin. This common glucose-lowering agent for diabetes has been safe, effective and globally affordable for over 60 years. Research into the use of metformin and its beneficial influence on healthy ageing is currently emerging. Although metformin’s effect on clinical ageing outcomes may be speculative, findings from studies into cellular and animal models and from observational and pilot human studies support its potential beneficial effects on ageing. Ageing has a significant impact on the cardiovascular system and is the leading non-modifiable risk factor for Cardiovascular Disease (CVD). The incidence and prevalence of CVD increases with advancing age, and CVD is the leading cause of death for populations over 65 years of age. However, most CVD prevention research has focused on development of interventions that target “traditional” CV risk factors such as hypertension, hypercholesterolaemia and diabetes. Metformin has been proposed to be an “anti-ageing” drug, based on preclinical experiments with lower-order organisms and numerous retrospective data on beneficial health outcomes for patients with type 2 diabetes. At present, randomised clinical trials to evaluate metformin’s clinical impact on healthy ageing are limited. Here, we review the role of metformin and its potential to reduce cardiovascular events in the healthy elderly.